MUSE – Mission to the Uranian system: Unveiling the evolution and formation of ice giants. Issue 9 (1st May 2015) - Bocanegra-Bahamón, Tatiana; Bracken, Colm; Costa Sitjà, Marc; Dirkx, Dominic; Gerth, Ingo; Konstantinidis, Kostas; Labrianidis, Christos; Laneuville, Matthieu; Luntzer, Armin; MacArthur, Jane L.; Maier, Andrea; Morschhauser, Achim; et al.
Abstract: The planet Uranus, one of the two ice giants in the Solar System, has only been visited once by the Voyager 2 spacecraft in 1986. Ice giants represent a fundamental class of planets, and many known exoplanets fall within this category. Therefore, a dedicated mission to an ice giant is crucial to improve the understanding of the formation, evolution and current characteristics of such planets in order to extend the knowledge of both the Solar System and exoplanetary systems. In the study at hand, the rationale, selection, and conceptual design for a mission to investigate the Uranian system, as an archetype for ice giants, is presented. A structured analysis of science questions relating to the Uranian system is performed, categorized by the themes atmosphere, interior, moons and rings, and magnetosphere. In each theme, science questions are defined, with their relative importance in the theme quantified. Additionally, top-level weights for each theme are defined, with atmosphere and interior weighted the strongest, as they are more related to both exoplanetary systems and the Uranian system, than the other two themes (which are more specific for the planet itself). Several top level mission architecture aspects have been defined, from which the most promising concepts were generated using heuristic methods. A trade-off analysis of these concepts is presented, separately, for engineering aspects, such as cost, complexity, and risk, and for science aspects. The science score for each mission is generated from the capability of each mission concept to answer the science questions. The trade-off results in terms of relative science and engineering weight are presented, and competitive mission concepts are analyzed based on the preferred mission type. A mission design point for a typical flagship science mission is selected from the trade space. It consists of a Uranus orbiter with a dry mass of 2073 kg including 402 kg of payload and a Uranus entry probe, which is to perform measurements down 100 bar atmospheric pressure. The orbiter science phase will consist of a Uranus orbit phase of approximately 2 years in a highly elliptical orbit, during which 36 Uranus orbits are performed. Subsequently, a moon phase is performed, during which the periapsis will be raised in five steps, facilitating 9 flybys of each of Uranus' major moons. A preliminary vehicle design is presented, seeking the best compromise between the design drivers, which basically derive from the large distance between Uranus and the Earth (e.g., high thermal load during Venus flyby, low thermal load during Uranus science phase, low data-rate during Uranus science phase, the need of radioisotope power source, etc). This paper is the result of a study carried out during the Alpbach Summer School 2012 "Exploration of the icy planets and their systems" and a one-week follow-up meeting in Graz, Austria. The results of this study show that a flagship ESA L-class mission – consisting of an orbiter with a single atmospheric entry probe and flybys of the main satellites – would be able to address the set of science questions which are identified in the study at hand as the most essential for the understanding of Uranus and its system. The spacecraft, as currently designed, could be launched with an Ariane 5, in 2026, arriving at Uranus in 2044, and operating until 2050. The development of a radioactive power source is the main requirement for feasibility for this mission.